Nuclear analysis of the ITER torus cryopumps. (9th September 2019) - Pedroche, G.; Lopez-Revelles, A.J.; Kolsek, A.; Dremel, M.; Bansal, G.; Pearce, R.; Sanz, J.; Juarez, R.
Abstract: The ITER Tokamak will feature six torus cryopumps (TCP) to maintain the vacuum requirements inside the vacuum vessel for plasma operation. They will be connected to the ITER vacuum vessel through the lower ducts, which have limited shielding to ensure an efficient pumping. Therefore, these ducts will represent a relevant path for radiation to travel from the plasma and affect diverse aspects of the ITER facility, such as the electronics allocation or the maintenance operations during the machine shutdown. Previous analyses have addressed these important aspects. Nonetheless, limitations in those studies and design evolution have justified a new analysis, specifically dedicated to the TCP final design review. The results of the nuclear analysis are presented here focusing on the B1 level port cell #4. The TCP design and the associated and neighboring equipment have evolved and updated models have been considered. The TCP modelling has required an explicit heterogeneous treatment of the internal parts. The radiation source from the divertor cooling water pipes running along the port cell ceiling has been considered with the latest available source definition. In terms of methodology, one major improvement has been the modelling of the radiation transmission from C-model to the Tokamak Complex model. Another important improvement has been the consideration of D1SUNED for the determination of shutdown dose rates, covering a broader fraction of the radioactive inventory than in previous studies. The following quantities have been determined: neutron flux, absorbed dose to silicon, 1 MeV equivalent neutron fluence and shutdown dose rates (SDDR) after 10 6 s of cooling time. Finally, a set of proposals have been made to considerably mitigate the SDDR after 10 6 s of cooling. This work represents a realistic and matured source of information of the radiation environment in the ITER TCP port cells as presented in the final design review.